Analysis Juridical to Playback Movie Protection Drive-in by Meikarta based on Copyright Law - Elisabet Mariyani; Yuli Dinata Kusumaningrum (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2022)
Intellectual Property Rights are creations or works originating from human ideas. Copyright is one of the rights protected by Intellectual Property Rights. Copyright protects several forms of work, one of which is film. Several months ago Meikarta held a drive -in event . Drive - in is the activity of watching movies via car. Drive -in is not strictly regulated in Law Number 28 of 2014 concerning Copyright. Therefore the author is interested in writing a paper entitled Main problems in this thesis into two, namely; What are the arrangements for drive -in screening of films based on Law Number 28 of 2014 concerning Copyright, and whether Meikarta committed a violation in carrying out drive -in screening of films as stipulated in Law Number 28 of 2014 concerning Copyright. In this study using normative research methods with qualitative data analysis. The results of the study illustrate that setting movie playback with the drive -in method is permissible however still have to ask permission from the Copyright Holder or Creator. And must still pay attention to the provisions of Law Number 28 of 2014 concerning Copyright. Meikarta has violated Article 9 paragraph (2) and (3), as well as Article 113 of Law Number 28 of 2014 concerning Copyright.